Potential Of Kenikir (Cosmos Caudatus Kunth) Leaves Essential Oil Against Candida Albicans Atcc 10231 In Vitro: Potential Of Kenikir (Cosmos Caudatus Kunth) Leaves Essential Oil Against Candida Albicans Atcc 10231 In Vitro - Siti Zainatun Wasilah; Ratih Hardisari; Budi Martono; Wahyu Adi Pratama (Medica Hospitalia : Journal of Clinical Medicine, 2022)
BACKGROUND : Kenikir is a medicinal plant whose leaves are often consumed as vegetables. Kenikir leaves contain active compounds such as flavonoids, polyphenols, saponins, tannins, alkaloids and essential oils. These compounds are thought to be able to inhibit the growth of Mycobacterium tuberculosa and Candida albicans ATCC 10231 strains OBJECTIVE : The purpose of this study was to describe the effect of kenikir leaf essential oil on the growth of the Candida albicans ATCC 10231 strains. with 4 concentrations and 6 repetitions in Candida albicans and the concentration of kenikir leaf essential oil concentration of 0.5%, 1%, 1.5%, 2%, METHOD : This type of research is a pure experimental research by providing treatment in the form of giving essential oil of kenikir leaves with various concentrations on the growth of the Candida albicans ATCC 10231 strains. The inhibition test of kenikir leaf essential oil on the growth of the  Candida albicans ATCC 10231 strains was carried out using the Kirby Bauer disk diffusion method. The research design used is Post Test Only with Control Group Design.Data obtained in the form of inhibition zone diameter, were analyzed using Variant Analysis (Anova), P£ 0,05 and continued with Post Hoc test. RESULT : The results showed that 0.5% essential oil concentration had a inhibition zone of 9.67 mm (moderate criteria); essential oil concentration of 1% with a inhibition zone of 9.72 mm with criteria moderate and 1.5% concentration with inhibition zone 11.86% with strong criteria and concentration 2% with inhibition zone 12.67 mm with strong criteria all concentrations affect the growth of Candida albicans  with the most optimal concentration of 2% for the Candida albicans ATCC 10231 strains. CONCLUSION : The higher the concentration of kenikir leaf extract, the inhibitory effect on the growth of Candida albicans ATCC 10231 strains was also higher. KEYWORDS : Cosmos caudatus Kunth, Candida albicans ATCC 10231 strains, diameter of the inhibition zone